Komunikasi Dakwah Zaman Milenial - Muslimin Ritonga (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2019)
In this modern era, technology is growing rapidly. The internet and other social media seem to have become important needs for millennial generations. The use of social media has touched various walks of life, ranging from urban communities to rural and remote areas, both children, adolescents, to adults can be sure to have tasted various kinds of social media such as Facebook, Instagram, Twitter, Youtube, WhatsApp and others. This media tool is very good if it is used for useful things such as preaching. Millennial preaching must use it as much as possible. If not, the flow of da'wah is slowing down and lagging behind. This study discusses the impact of information globalization which is marked by advances in communication technology and is associated with the readiness of da'i in utilizing social media and delivering da'wah.